Early onset of cannabis use and alcohol intoxication predicts prescription drug misuse in American Indian and non-American Indian adolescents living on or near reservations. (3rd July 2020) - Stanley, Linda R.; Swaim, Randall C.; Smith, Joey K.; Conner, Bradley T.
ABSTRACT: Background: Prescription drug misuse (PDM) is a growing issue within the American Indian (AI) population, especially in younger populations. Objectives: This study estimates relationships between PDM and early initiation (prior to 14 yrs) of cannabis use and alcohol intoxication for a national sample of AI and non-AI adolescents attending schools on or near reservations. Method: Participants were 2580 students (50.2% female; 58.1% AI), ages 15–18, attending schools located on or near an AI reservation. Four models of PDM were estimated: 1) demographic variables; 2) demographics plus cannabis use initiation status; 3) demographics plus alcohol intoxication initiation status; and 4) all variables. All analyses were conducted using multilevel modeling. Results: Results indicated that early onset of cannabis use and alcohol intoxication were individually significant predictors of PDM for AI and non-AI adolescents, with odds ratios (OR) of 47.00 for cannabis (p <.01) and 35.73 (p <.01) for intoxication and with no significant differences by race (AI vs. non-AI). Results also indicated a greater likelihood of PDM when a student was an early initiator of both cannabis use and intoxication than when they were one or the other. Finally, there was a significantly greater association between cannabis use and PDM (ORearlycannabis = 24.95, p <.01) than between intoxication and PDM (ORearlyintoxication = 3.98, p <.01) when both predictors were in the model. Conclusions: These findings suggest that for AI and non-AI youth who have some shared living experience, early initiation of cannabis use and alcohol intoxication are risk factors that are similarly related to PDM and that targeting early initiation for both groups of adolescents is critical in prevention of PDM.